Class Struggle and Systematic Exploitation: A Marxist Analysis of Social Inequality in "The Purge: Anarchy" (2014) - Ravinda Syaiful Bustammmi; Teguh Kasprabowo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study examines the representation of class struggle and systematic exploitation in "The Purge: Anarchy" (2014) through a Marxist theoretical framework to understand how contemporary dystopian cinema critiques capitalist social relations. The research addresses how the film represents class struggle and illustrates systematic exploitation as mechanisms of social control using qualitative descriptive methodology with Marxist literary criticism approach. Analysis was conducted through multiple systematic viewings of the film, focusing on character interactions, narrative structures, and visual elements that demonstrate class conflict and social inequality. The main findings reveal that the film effectively portrays class struggle through character conflicts that embody class tensions, spatial arrangements that physically manifest class divisions, and narrative structures that reveal institutional mechanisms of oppression. The study demonstrates that systematic exploitation is illustrated through power dynamics between social classes, government institutions that facilitate class-based violence, and visual representations that make economic inequality concrete and immediate. The film's hunting auction scenes, where wealthy elites pay $200,000 to hunt poor citizens, exemplify how dystopian narratives transform abstract Marxist concepts into visceral narrative events accessible to mainstream audiences. The research concludes that "The Purge: Anarchy" succeeds as a contemporary critique of capitalism by integrating class struggle and systematic exploitation as interconnected mechanisms. The film uses its dystopian setting to make visible the violence underlying everyday capitalist relations while serving as a vehicle for developing class consciousness through popular entertainment.